Awareness of sudden infant death syndrome and its associated risk factors among Saudi mothers attending well-baby clinics at PHC, PSMMC, Riyadh, Saudi Arabia: A cross-sectional study - Saleh L. Alanezi; Yousef A. Almusalam; Aymen A. Afify (Journal of Family Medicine and Primary Care)
Introduction: Sudden infant death syndrome (SIDS) is a leading cause of infant mortality all over the world. Mortality due to SIDS can be averted by educating families and caretakers about safe practices for putting infants to sleep. However, the knowledge, attitude, and practices of mothers while putting the infant to sleep is a gray areas in literature. Aims and Objectives: The objectives of the study were to measure the knowledge and awareness about SIDS and its associated risk factors practiced among Saudi mothers attending well-baby clinics in Saudi Arabia to develop appropriate educational program-based interventions for safe practices of infant care. Methods: This cross-sectional study was carried out among 385 mothers attending well-baby clinics of primary health care (PHC) and prince sultan military medical city (PSMMC) in Riyadh Saudi Arabia. Information was captured on sociodemographic characteristics, the health status of mothers and infants, knowledge, attitude, and practice followed by mothers while putting infants to sleep. Results: From a total number of 385 responses, 350 participants were eventually included in the final sample due to the incompletion of the questionnaire of 350 mothers; only 26% (n = 93) mothers had heard of SIDS. However, 259 mothers were willing to attend the awareness session. Only 94 mothers had knowledge as well as practicing the correct behavior of putting the infant to sleep on the back referred to as “good behavior concordant pairs.” Similarly, other good practices include not co-sharing a bed with the infant, removing pillows, blankets, and other wedged objects, using a pacifier, breastfeeding the infant during sleep, not using multiple quilts, not covering the infant’s head with a quilt, not using a head cap. The number of good behavior concordant pairs (in green) were 124, 38, 56, 98, 18, 117, and 68 respectively. Conclusions: The rate of knowledge and practice for good behavior regarding SIDS was low among Saudi mothers in Riyadh Saudi Arabia. SIDS-related deaths can be averted by improving the understanding of SIDS risk reduction practices among mothers by using health promotion strategies.